2014
DOI: 10.1111/jai.12443
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships and growth parameters of two endemic fish species (Floridichthys polyommusHubbs, 1936 andFundulus persimilisMiller, 1955) from the Yucatan Peninsula, Mexico

Abstract: Summary This study reports length‐weight relationships and growth parameters for Floridichthys polyommus Hubbs, 1936 and Fundulus persimilis Miller, 1955 from La Carbonera, a karstic tropical coastal lagoon on the northwestern coast of the Yucatan Peninsula, Mexico. Specimens were collected between April 2009 and March 2010. The resulting length‐weight relationship for F. polyommus was: W = 0.0180 Lt3.37 and W = 0.0142 Lt3.35 for F. persimilis. This study presents the first estimation for both species of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…The maximum SL recorded for F. polyommus in this study was 80 mm. This figure differs from the maximum SL reported elsewhere for this species: 195 mm SL in Celestun Lagoon (Vega‐Cendejas, de Santillana, & Arceo, ); 91 mm SL in Ría Lagartos, Yucatán (Peralta‐Meixueiro & Vega‐Cendejas, ); and 103 mm SL in La Carbonera, Yucatán (Badillo‐Alemán, Bonilla‐Gómez, Tzeek‐T, Gallardo‐Torres, & Chiappa‐Carrara, ). The differences in SL between Champotón River and Celestun Lagoon may be due to that Celestun is a meso‐eutrophic coastal lagoon that is highly productive throughout the year, with a substantial contribution to productivity by macroalgae and seagrass (Herrera‐Silveira, Medina‐Gomez, & Colli, ).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The maximum SL recorded for F. polyommus in this study was 80 mm. This figure differs from the maximum SL reported elsewhere for this species: 195 mm SL in Celestun Lagoon (Vega‐Cendejas, de Santillana, & Arceo, ); 91 mm SL in Ría Lagartos, Yucatán (Peralta‐Meixueiro & Vega‐Cendejas, ); and 103 mm SL in La Carbonera, Yucatán (Badillo‐Alemán, Bonilla‐Gómez, Tzeek‐T, Gallardo‐Torres, & Chiappa‐Carrara, ). The differences in SL between Champotón River and Celestun Lagoon may be due to that Celestun is a meso‐eutrophic coastal lagoon that is highly productive throughout the year, with a substantial contribution to productivity by macroalgae and seagrass (Herrera‐Silveira, Medina‐Gomez, & Colli, ).…”
Section: Discussioncontrasting
confidence: 85%
“…() in Celestun Lagoon ( b = 3.31) and Badillo‐Alemán et al. () in La Carbonera, Yucatán ( b = 3.55 males; 3.38 females). The b value detected in our study is similar to the one reported for the Cyprinodontid genus Aphanius (Yoğurtçuoğlu & Ekmekci, ).…”
Section: Discussionmentioning
confidence: 88%